Simulation of a supply chain game with multiple fuzzy goals - Yuh-Wen, Chen; Larbani, Moussa; Chen-Hao, Liu (Elsevier, 2010)
Supply chain management(SCM)issues have been popularly discussed in recentyears. However, few papers in past literature have been dedicated to the use the fuzzy multi-objective-game framework for analyzing how the strategic partnership influences individual and global performance in a supply chain. This study formulates a game framework for the investigation of strategic behavior of supply chain partners based on fuzzy multi-objective programming the alliance matrix and achievement level/aspiration degree. This work assumes the partners as having multiple objective and the supply chain is multi-product and multi-material. To validate our model we simulate the micro-and macro-performance of a supply chain by the achievementlevel under various partner alliances. In addition,a sensitivity analysis is conducted.Finally, some useful lessons are summarized.